KARAKTERISTIK PERAMBATAN RETAK FATIK VELG HASIL CENTRIFUGAL CASTING PUTARAN RENDAH DENGAN PERLAKUAN T6 - , REZA WIRAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Cast wheel is a vehicle component that when in used will get dynamic load. Recurring expense will cause fatigue. So that this product must have guaranty on failure caused by fatigue and save in used and also have useful life time. This research determined to find the quantitative relationship between the effect of T6 heat treatment with artificial aging temperature variation on the fatigue characteristics of aluminium A356 centrifugal casting velg. The material used in this study was aluminum alloy A356. The specimens were made based on ASTM E647. This research uses five types of specimens, one of the specimen without T6 heat treatment process and the others were subjected to T6 heat treatment. Variations T6 heat treatment was conducted at a temperature of 5350C heating specimen with holding time for 4 hours and then continued with aging at temperatures 300C, 1500C, 1750C, and 2000C with holding time of 4 haours. Then the whole specimen tested with crack propagation of stress ratio R = 0,1. The composition test results show that the centrifugal casting wheel was made of aluminium alloy A356 with main compotition of Al, Si, and Mg. The crack propagation test results on specimens without heat treatment with R = 0,1 gives the Paris value C=2E-11 dan n=4,823. Specimen with T6 heat treatment with aging temperature 300C, 1500C, 1750C, and 2000C respectively Paris has a value of C=3E-12 and n=3,899, C=2E-11 and n=3,737, C=6E-12 and 3,424, and C=8E-12 dan n=3,872.